Ethnic differences in time to surgery for women with early stage breast cancer in Aotearoa/New Zealand: a population-based studyResearch in context - Leah Boyle; Ross Lawrenson; Maxine Ronald; Ian Campbell; Vili Nosa; Sandar Tin Tin (Elsevier, 2024)
Summary: Background: This study evaluates whether there are ethnic differences in time to surgery in women with early-stage (1-3a) breast cancer in four NZ urban regions between 2000 and 2020 pre- and post- Faster Cancer Treatment (FCT) implementation, which was introduced to address inequities in cancer outcomes. Methods: This retrospective analysis used Te Rēhita Mate Ūtaetae (Breast Cancer Foundation National Register), a prospectively maintained database of breast cancers from 2000 to 2020. Women with stage 3b, 3c, metastatic or bilateral cancers were excluded. Logistic regression models evaluated ethnic differences in time to surgery (≤31/>31 days as per FCT plan) with sequential adjustment for potential contributing factors (demographic, mode of diagnosis, tumour, treatment facility type and treatment). Subgroup analyses by pre- and post-FCT implementation date were undertaken. Findings: Of the 16,365 women included, 74.1% were NZ European (NZE), 10.2% were Māori, 6.1% were Pacific, and 9.2% were Asian. Wāhine Māori (Māori women) and Pacific women were more likely to experience delays in surgery >31 days, compared to NZE (maximally adjusted OR: 1.18; 95% CI:1.05, 1.33 and OR:1.42; 95% CI:1.22, 1.65, respectively)-deprivation and treatment facility type contributed most to this. Wāhine Māori experienced delay in the public system only. The associations did not differ between the pre- and post- FCT periods. Interpretation: Ethnic inequities exist with respect to time to surgery for women with early-stage breast cancer and these differences persist after FCT implementation. Funding: LB is supported by the Richard Stewart scholarship, the Royal Australasian College of Surgeons and Oxford Population Health.